2017
DOI: 10.1080/02770903.2017.1323921
|View full text |Cite
|
Sign up to set email alerts
|

Overweight adolescents and asthma: Revealing motivations and challenges with adolescent-provider communication

Abstract: Objective-Among teens with asthma, challenges of disease management may be greater in those with a body mass index (BMI) >85th percentile compared to youth within the parameters for normal weight-for-age. This mixed-methods study assessed teens' awareness of the link between weight and asthma management, and perspectives on how medical providers might open a discussion about managing weight.Method-Teens aged 13-18, having BMI >85 percentile and chronic asthma, identified using health system databases and a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Experienced reviewers (G.L.A., H.O. ), who participated in running the focus groups and who have previously worked on focus group research published in peer-reviewed publications, [11][12][13] read through each transcript at least 2 times and entered relevant topics and direct quotes. Separately, the study principal investigator (G.W.)…”
Section: Methodsmentioning
confidence: 99%
“…Experienced reviewers (G.L.A., H.O. ), who participated in running the focus groups and who have previously worked on focus group research published in peer-reviewed publications, [11][12][13] read through each transcript at least 2 times and entered relevant topics and direct quotes. Separately, the study principal investigator (G.W.)…”
Section: Methodsmentioning
confidence: 99%
“…Other barriers to providing support included limited resources and a poor awareness (or existence) of referral pathways. Frustration with this lack of support services mirrored an overweight adolescent asthma sample who expressed unhappiness at weight concerns being raised in consultations without HCPs being able to provide further intervention (32). In addition, the hospital-based HCPs in this study felt that delivery of behaviour change support was better placed within community care settings, as found previously in other specialised HCPs (33).…”
Section: Discussionmentioning
confidence: 55%
“…More research has been focused on capturing the child's view of symptom management and how children perceive taking medication in recent years. A recent study explored the motivations and challenges of communication between overweight adolescents with asthma and their HCP (Alexander, Olden, Troy, Miree, & Joseph, 2018). The author found that the children valued their providers' communication with them.…”
Section: Discussionmentioning
confidence: 99%